HUBUNGAN KUALITAS TIDUR DAN KECEMASAN DENGAN KEJADIAN SLEEP PARALYSIS PADA MAHASISWA PENDIDIKAN DOKTER UNIVERSITAS SYIAH KUALA - Suherman, Suherman; Razali, Rezania; Helmi, Denada Putri (Buletin Farmatera, 2021)
Sleep paralysis is a sleep disorder classified as a rapid-eye-movement (REM) sleep-related parasomnia which is characteristic of the inability to perform voluntary movements at sleep onset or on awakening. Medical students have a high academic burden that causes physical and mental problems such as poor sleep quality and anxiety that are risk factors for sleep paralysis. This research aims to determine the relationship between sleep quality and anxiety with the incidence of sleep paralysis among Medical Students of Universitas Syiah Kuala. These three variables were measured by Pittsburgh Sleep Quality Index (PSQI), State-Trait Anxiety Inventory-Trait (STAI-T), and modified Unusual Sleep Experience Questionnaire (USEQ) respectively. The type of research is an analytical observational study with a cross-sectional design. The sample is 216 respondents who are taken by proportional random sampling. The statistical analysis of the research was analyzed using the contingency lambda test and logistic regression test. The result of the research showed that 86.3% of respondents experienced poor sleep quality with sleep paralysis and 78,4% of respondents experienced anxiety with sleep paralysis. This study concludes that there is a significant relationship between sleep quality and anxiety with the incidence of sleep paralysis.